Liver Dysfunction in Hyperemesis Gravidarum - Zafar Shah, Humaira Bibi, Shamim Akhtar, Noor-ul-Amin, Saba Nasir, Bushra Sadia (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of liver dysfunction in patients with hyperemesis gravidarum. Study design: It was a retrospective cross sectional study. Place and duration: This study was done in the gastroenterology department of Timergara Teaching Hospital over a period of 1 year i.e., from September 2021 to August 2022. Methods: 140 pregnant women admitted with diagnosis of hyperemesis gravidarum were included in this study after excluding liver disease. Data was collected from case files from the department of medical records. SPSS version 25 was used to analyze the data. Results: Liver dysfunction was seen in 55.2% of patients with hyperemesis gravidarum. The mean age of patients with hyperemesis gravidarum was found to be 24.4±5.35 years and most cases were found to be primigravida i.e., 72.8%. Mean gestational age was found to be 9.2± 1.9 weeks. No significant difference in liver dysfunction was seen in relation to BMI. Conclusion: Abnormal liver function tests is a common finding in cases of hyperemesis gravidarum which recover completely when resolution of hyperemesis occurs and needs no treatment. Key words: Hyperemesis gravidarum, nausea and vomiting of pregnancy, liver dysfunction, liver function tests. ALT, AST.